Interpersonal closeness and morality predict feelings of being moved - Seibt, C. (2017)
The emotion commonly labeled in English as being moved or touched is widely experienced but only tacitly defined, and has received little systematic attention. Based on a review of conceptualizations from various disciplines, we hypothesize that events appraised as an increase in interpersonal closeness, or as moral acts, when sufficiently intense, elicit a positive emotion typically labeled "being moved," and characterized by tears, goosebumps, and a feeling of warmth in the chest. We predicted this to be true for events a person participates in, as well as for events they observe. In Study 1, we elicited reports of recent episodes of weeping evoked by something positive, and also weeping because of something negative; we measured emotion terms, bodily sensations, and appraisals in a U.S. sample. We discovered that events of positive tears, rather than negative tears, were associated with self-reported being moved or touched, with goosebumps, with feelings of chest warmth, and with the appraisals of increased closeness and moral acts. These appraisals mediated the difference in being moved between positive and negative events. We further found that appraisal patterns for personally experienced events were similar to the patterns for observed events. Finally, the 2 appraisals were more closely associated with being moved than with other emotion labels. This was corroborated in Study 2 in the U.S. and Norway, where we induced being moved, sadness, anxiety, and happiness through videos and measured these emotions, plus the appraisals and sensations from Study 1.